A Krukenberg tumor case presenting with hirsutism - (:unkn) unknown (My University, 1996)
Metastatic ovarian tumors which have gastric origin are called Krukenberg tumors. A twenty eight years old woman was admitted to our clinic with a history of abdominal pain, weight loss and signs of hirsutism. Abdominal and pelvic examinations revealed a solid mass above the umblicus and a mobile mass in the right adnexial region. Ultrasonographic findings confirmed a solid mass at the right adnexial area with fluid in the Douglas pouch, an enlarged liver and a thickened stomach wall suggesting metastatic ovarian cancer. The biopsy taken during endoscopy revealed a gastric carcinoma. The unexpected hirsutism symptoms of the patient did not have any correlation with her serum testesterone and DHEA-S levels. The persent article reports a Krukenberg case with endocrine activity.
Keywords: Hirsutism; Krukenberg tumor